Perlocutions of 2024 Indonesian General Election: A Cyberpragmatics Perspective - Lailiyah, Nur (Universitas Gadjah Mada, 2024)
Studies on cyberpragmatics have revealed that perlocution or an act of speaking for persuasion the meaning of language can no longer be solely interpreted from traditional pragmatic perspectives. This is especially the case in the context of rapid technological advancement. Built on this cyberpragmatics theory on the function of language, this study aims to describe the perlocutions of the 2024 elections on social media from a Cyberpragmatics perspective. Drawing on descriptive qualitative method, this study focuses on the manifestations of perlocution in netizens' comments about the 2024 elections. The research data comprises excerpts of utterances containing manifestations of the 2024 election perlocutions. The substantive data sources for this research are written texts found on social media, specifically from the official cnnidpolitik account in July 2023 with the theme